Buddhism in China - Laolook-in, Panchaporn; Poonwiwat, Wararak; Kritthanawat, Suthima (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
This academic article aims to say the history and origins of Buddhism in China. Chinese Buddhism patterns and the role of Buddhism in China today by collecting data from research papers, books, journals and articles to analyze, process and summarize content for the purposes set out above. This is expected to be beneficial to the study of Chinese culture, especially to those interested in the cultural beliefs of the Chinese people. The result of the study found that Buddhism entered China in the Han Dynasty and the first Buddhist temple was built in China. Later, the Tang Dynasty was considered the most prosperous era of Buddhism in China because the emperor has the corrupt faith in Buddhism. So, he patronized Buddhism and sent monks to India and brought the Tripitaka back to China and there have been many translations of the Sutra from Pali into Chinese. After that, Buddhism gradually deteriorated until in the Qing Dynasty, the king would pay more attention to Tibetan Vajrayana Buddhism until the Cultural Revolution of President Mao Zedong, many temples and scriptures were burned down because religious beliefs and cults were considered a threat to the Chinese Communist Party. It is considered the depressing era of Buddhism in China. After that, in the era of President Deng Xiaoping, this rule was loosened, thus making Buddhism in China more attractive to the outside world and developed to become the Chinese Buddhism that we have seen today.